ARCHITECTURE OF MODERN SECURED INFORMATION & COMMUNICATION AIRPORT NETWORK - Ткаліч, Олег Петрович; Одарченко, Роман Сергійович; Гнатюк, Сергій Олександрович (Ukrainian Information Security Research Journal, 2015)
Modern airport should provide on-time quality and securedservices to their customers. The increasing of theseservices (according to information and communicationtechnology develop ent) and number of passengers impetusto searching and implementation new concepts andapproaches to integrated information services providingin airports. Certainly the unified information & communicationnetwork creation is very important. This can providea high level of information services to network subscribers.Also this network will be secured for users andcan integrate security means, call centers, entertainmentcontent, video monitoring systems, passengers registrationsystems, information of airport operating agency,sensor networks for intellectual management of life sustainingairport systems, cellular communication operators,modern concepts like SDN, SDR, BYOD and ІоТ. Inthis context this paper presents integration of mentionedmodern and prospective concepts and technologies forairport corporate network`s architecture and topologyoptimization. Given results give possibility to increase theeconomic efficiency of airport corporate network using.Also it enables high security of the network, informationservices quantity and quality increasing, simplify the managementof network and life sustaining airport systems.